Human Milk and Lactation - Gianni, Maria Lorella (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Human milk is uniquely tailored to meet infants’ specific nutritional requirements. However, it is more than just “milk”. This dynamic and bioactive fluid allows mother–infant signalling over lactation, guiding the infant in the developmental and physiological processes. It exerts protection and life-long biological effects, playing a crucial role in promoting healthy growth and optimal cognitive development. The latest scientific advances have provided insight into different components of human milk and their dynamic changes over time. However, the complexity of human milk composition and the synergistic mechanisms responsible for its beneficial health effects have not yet been unravelled. Filling this knowledge gap will shed light on the biology of the developing infant and will contribute to the optimization of infant feeding, particularly that of the most vulnerable infants. Greater understanding of human milk will also help in elucidating the best strategies for its storage and handling. The increasing knowledge on human milk’s bioactive compounds together with the rapidly-advancing technological achievements will greatly enhance their use as prophylactic or therapeutic agents. The current Special Issue aims to welcome original works and literature reviews further exploring the complexity of human milk composition, the mechanisms underlying the beneficial effects associated with breastfeeding, and the factors and determinants involved in lactation, including its promotion and support.